Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.15252/embj.2021108664
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor BES1 interacts with HSFA1 to promote heat stress resistance of plants

Abstract: Heat stress is a major environmental stress type that can limit plant growth and development. To survive sudden temperature increases, plants utilize the heat shock response, an ancient signaling pathway. Initial results had suggested a role for brassinosteroids (BRs) in this response. Brassinosteroids are growth-promoting steroid hormones whose activity is mediated by transcription factors of the BES1/BZR1 subfamily. Here, we provide evidence that BES1 can contribute to heat stress signaling. In response to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 86 publications
1
37
0
Order By: Relevance
“…Studies in Arabidopsis and tomato demonstrate that downstream of BRs signaling, but not BRs level, make sense in heat stress response (Mazorra et al, 2011;Setsungnern et al, 2020). Similarly, a latest study reveals that BES1 is rapidly dephosphorylated and activated by heat stress in a manner independent of BRs signaling (Albertos et al, 2022). It seems like a paradox that BRs activate BES1/BZR1 but endogenous BRs levels are indispensable for thermal tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies in Arabidopsis and tomato demonstrate that downstream of BRs signaling, but not BRs level, make sense in heat stress response (Mazorra et al, 2011;Setsungnern et al, 2020). Similarly, a latest study reveals that BES1 is rapidly dephosphorylated and activated by heat stress in a manner independent of BRs signaling (Albertos et al, 2022). It seems like a paradox that BRs activate BES1/BZR1 but endogenous BRs levels are indispensable for thermal tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicates that a defect in BES1 showed serious sensitive characteristics to heat stress compared to wild type. Heat shock rapidly activates BES1 and ABA promotes the dephosphorylation of BES1 through repressing the activity of PP2C-type phosphatases in HS process (Albertos et al, 2022). HSP90 forms a complex with BES1 and assists the compartmentalized cycle between active and inactive BES1 (Samakovli et al, 2020;Shigeta et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations